Clinical implications of proximal tubular multicilia in glomerular diseases - Bohye Kim; Boram Weon; Evonne Kim; Sohee Park; Wencheng Jin; Nayeon Shin; Yun Kyu Oh; Chun Soo Lim; Jung Pyo Lee; Obin Kwon; Jeonghwan Lee (Heliyon)
Introduction: Multiciliated cells (MCCs) have been identified in the proximal tubules of patients with kidney disease; however, their clinical significance is unknown. We aimed to investigate whether MCCs are associated with clinical outcomes in patients with glomerular diseases. Methods: Between August 2012 and April 2021, 134 patients (including 126 with glomerular disease patients and 8 controls) who were hospitalized at Seoul National University Boramae Medical Center and Seoul National University Hospital were included in this study. The ratio of MCCs to total proximal tubular cells was calculated using immunohistochemistry. The relationship between the MCC ratio and kidney disease-related clinical features was then analyzed. Results: MCCs were exclusively detected in patients with glomerular diseases (68.3 %), not those in the control group. Patients with diabetic kidney disease (88.9 %) or antineutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (GN, 86.4 %) had higher MCC ratios. MCC-positivity and MCC ratios were significantly associated with increased age and proteinuria, and a decreased estimated glomerular filtration rate (eGFR). Patients with higher MCC ratios had a significantly higher risk of end-stage kidney disease (ESKD) and composite outcomes with death. In multivariable analysis, MCC ratios were significantly correlated with an increased risk of ESKD (hazard ratio [HR], 1.413; 95 % confidence interval [CI], 1.012–1.972) and composite outcome (HR, 1.401; 95 % CI, 1.028–1.909). Conclusion: Higher MCC ratios were correlated with poorer prognosis; therefore, quantification of MCCs in the proximal tubules can serve as a valuable prognostic marker in clinical practice.